Thermal performance in layer hen house with natural acclimatization - Biaggioni, Marco Antônio Martin [UNESP]; De Mattos, Juliana Medeiros [UNESP]; Jasper, Samir Paulo [UNESP]; Targa, Luiz Antônio [UNESP] (My University, 2008)
The work aimed at presenting analyses and comparisons of the thermal performance of a laying hens housing in the region of Bastos, in the state of São Paulo, adapted from natural alternatives of acclimatization, having a not adapted housing as reference, that is, of a more common typology in the area, and another one, artificially acclimatized. The index evaluated was the temperature and humidity (THI), the black globe temperature and humidity index (GTHI) and the thermal radiation charge (TRC). It was calculated from the measurement of the temperature of dry bulb, temperature of wet bulb, temperature of black globe and air speed. The measurements were made both in the intern and the extern environment, at four times (5 a.m, 11a.m., 3 p.m. and 4 p.m. o'clock) and in two seasons (late spring and early summer), for ten days in a row. The results allow to conclude that the house naturally acclimatized (NA) has presented intermediate performance as compared with the others, making it to possible to control environment at adequate levels only during spring.
Desempenho térmico de aviário de postura acondicionado naturalmente
Keywords: Poultry; Rural building; Thermal comfort